2011
DOI: 10.4103/0975-7406.76491
|View full text |Cite
|
Sign up to set email alerts
|

Importance of phenols structure on their activity as antinitrosating agents: A kinetic study

Abstract: Objective:Nitrosative deamination of DNA bases induced by reaction with reactive nitrogen species (RNS) has been pointed out as a probable cause of mutagenesis. (Poly)phenols, present in many food items from the Mediterranean diet, are believed to possess antinitrosating properties due to their RNS scavenging ability, which seems to be related to their structure. It has been suggested that phenolic compounds will react with the above-mentioned species more rapidly than most amino compounds, thus preventing dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Approximately 50% of CRC are known to harbor mutated KRAS, namely a G > A transition at codons 12 or 13, which are characteristic of NOC-mediated DNA alkylation ( 77 ). NOCs have also been shown to induce DNA deamination leading to DNA polymerase and mismatch errors, and the formation of abasic sites ( 78 ). Evidence suggests guanine residues are more sensitive to N -nitroso deamination than adenine and cytosine ( 78 ).…”
Section: Eating Pattern and Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 50% of CRC are known to harbor mutated KRAS, namely a G > A transition at codons 12 or 13, which are characteristic of NOC-mediated DNA alkylation ( 77 ). NOCs have also been shown to induce DNA deamination leading to DNA polymerase and mismatch errors, and the formation of abasic sites ( 78 ). Evidence suggests guanine residues are more sensitive to N -nitroso deamination than adenine and cytosine ( 78 ).…”
Section: Eating Pattern and Crcmentioning
confidence: 99%
“…NOCs have also been shown to induce DNA deamination leading to DNA polymerase and mismatch errors, and the formation of abasic sites ( 78 ). Evidence suggests guanine residues are more sensitive to N -nitroso deamination than adenine and cytosine ( 78 ). Cooking of meat at high temperatures generates heterocyclic amines (HCA) and polycyclic aromatic hydrocarbons (PAH) ( 79 , 80 ).…”
Section: Eating Pattern and Crcmentioning
confidence: 99%
“…Rambo et al (2021), like this study, identified guaiacol (28.7%) and creosol (22.5%) compounds in bio-oil derived from baru hydrolyzed endocarp. Bioproducts observed in this research have a wide range of industrial applications, a high market value, and a suitable use in biorefinery processes (Pessêgo et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…The holocellulosic fraction, which represents the sum of cellulose and hemicellulose contents in cupuaçu husk (59.6%), was significantly higher than others raw biomass found in cocoa shell (38.8%) (Hoyos et al, 2020) and pequi shell (41.6%) (Scapin et al, 2020), for instance, and similar to the baru mesocarp (59.3%) found by Rambo et al (2020). Additionally, complementary methodologies for characterization of alpha-cellulose and hemicellulose (Pedrazzi et al, 2019) Additionally, it is employed in the food, cosmetics, and textile sectors, as well as in the recent synthesis of functional materials (Pessêgo et al, 2011;Albuquerque et al, 2021;Rahim et al, 2019).…”
Section: Biomass Chemical Characterization and Sugars Yieldmentioning
confidence: 90%